If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6p=9+3p
We move all terms to the left:
6p-(9+3p)=0
We add all the numbers together, and all the variables
6p-(3p+9)=0
We get rid of parentheses
6p-3p-9=0
We add all the numbers together, and all the variables
3p-9=0
We move all terms containing p to the left, all other terms to the right
3p=9
p=9/3
p=3
| 45+30n=165 | | Y=55x+12 | | 3x4−11x3+15x2−9x+2=0 | | 6p=3p+15 | | (x−1)2=4 | | (11x+4)2x=840 | | -3+p/3=-5 | | -3+p|7=-6 | | 11x+4*2x=840 | | (x)-6=186 | | 6x+6=786x=72 | | 30+4x=70 | | 10x-2=35x+5 | | -r+7(1+3r)=33+7r | | 1/2(6a-1)=2a-1 | | -5/6+c=11/2 | | 2.4=-t÷4.5 | | 2x+35=3x-40 | | 7p–89=5p–59 | | 1/2x-1/6-6x=-25/6 | | 2c–1=9c–57 | | 2c–1=9c–57, | | 3(x+5)=10(x+5) | | 35^2+12^2=c^2 | | 4-x.5=-16 | | c*10=33.50 | | 4d+1=7d= | | 3x+5=11x+5 | | 16=12x-2x^2 | | 10y=3y+49 | | 4r-4=8r= | | 3(x+5)=11(x+5) |